Ledvični kamni pri otrocih - Kersnik-Levart, Tanja (Medicinski razgledi, 2007)
This review article presents the incidence of nephrolithiasis in children. Although nephrolithiasis in children is a rare disease, it is very important to diagnose, as it can lead to chronic renal insufficiency. The diverse clinical picture and etiology of nephrolithiasis are also discussed. It is stressed that the etiology of nephrolithiasis in children is a very complex process which includes many closely intertwined factors. The most common causeof nephrolithiasis in children is a metabolic disturbance, which necessitates proper investigation. The article also includes a description of morphologic and laboratory studies, treatment and prognosis, as well as recommendations for appropriate follow-up of these children.
Keywords: Kidney Calculi; Ledvični kamni; Otrok; Etiology; ledvične bolezni; Diagnosis; Therapy; otroci; Child